Absence of synemin in mice causes structural and functional abnormalities in heart. (January 2018) - García-Pelagio, Karla P.; Chen, Ling; Joca, Humberto C.; Ward, Christopher; Jonathan Lederer, W.; Bloch, Robert J.
Abstract: Cardiomyopathies have been linked to changes in structural proteins, including intermediate filament (IF) proteins located in the cytoskeleton. IFs associate with the contractile machinery and costameres of striated muscle and with intercalated disks in the heart. Synemin is a large IF protein that mediates the association of desmin with Z-disks and stabilizes intercalated disks. It also acts as an A-kinase anchoring protein (AKAP). In murine skeletal muscle, the absence of synemin causes a mild myopathy. Here, we report that the genetic silencing of synemin in mice (synm −/−) causes left ventricular systolic dysfunction at 3 months and 12–16 months of age, and left ventricular hypertrophy and dilatation at 12–16 months of age. Isolated cardiomyocytes showed alterations in calcium handling that indicate defects intrinsic to the heart. Although contractile and costameric proteins remained unchanged in the old synm −/− hearts, we identified alterations in several signaling proteins (PKA-RII, ERK and p70S6K) critical to cardiomyocyte function. Our data suggest that synemin plays an important regulatory role in the heart and that the consequences of its absence are profound. Highlights: Synm −/− cardiac muscle shows structural and functional changes associated with hypertrophic and dilated cardiomyopathies. Cardiomyocytes isolated from synm −/− heart have altered calcium transients. Changes in signaling molecules, PKA-RII, ERK and p70S6K, occur in synm −/− heart.